2020
DOI: 10.1242/dev.191973
|View full text |Cite
|
Sign up to set email alerts
|

Kctd15 regulates nephron segment development by repressing Tfap2a activity

Abstract: A functional vertebrate kidney relies on structural units called nephrons, which are epithelial tubules with a sequence of segments each expressing a distinct repertoire of solute transporters. The transcriptional codes driving regional specification, solute transporter program activation, and terminal differentiation of segment populations remain poorly understood. Here, we demonstrate that the KCTD15 paralogs, kctd15a and kctd15b, function in concert to restrict distal early (DE)/thick ascending limb (TAL) s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…However, there are transcription factors necessary for the proper formation of these domains. In the DE, these include Iroquois homeobox transcription factors, irx1a and irx3b [ 21 , 62 , 85 ]. WISH analysis on gldc morphants revealed an increase in length in the domains expressing irx1a and irx3b .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are transcription factors necessary for the proper formation of these domains. In the DE, these include Iroquois homeobox transcription factors, irx1a and irx3b [ 21 , 62 , 85 ]. WISH analysis on gldc morphants revealed an increase in length in the domains expressing irx1a and irx3b .…”
Section: Discussionmentioning
confidence: 99%
“…104 Further, tight regulation of Tfap2a expression was found to be essential, and controlled by the paralogs potassium channel tetramerization domain containing 15a and 15b (kctd15a, 15b). 105 Interestingly, a study found similar localizations of TFAP2A and KCTD15 expression during human nephrogenesis suggesting possible conserved roles in development. 115,131,132 Conclusions and future directions While there have been substantial advances in understanding the molecular mechanisms dictating the intricate events resulting in kidney development, there remain a number of challenges.…”
Section: Nephron Terminal Differentiationmentioning
confidence: 94%
“…86 One premiere system has been the zebrafish embryonic kidney, or pronephros, where a growing list of genes and signaling pathways has been identified. [104][105][106][107][108][109][110][111][112][113][114] Recent evidence from human kidneys strongly suggests potential conservation in gene expression and function with their zebrafish counterpart. 104,115 Combining the large data sets of mice and human scRNA sequencing with the relative ease of loss of function studies in zebrafish could streamline an evolutionarily conserved pipeline of essential factors for nephrogenesis.…”
Section: Nephron Regionalizationmentioning
confidence: 99%
“…Further, this simple architecture enables the precise visualization of each nephron lineage as it emerges [ 92 , 93 , 94 ]. The nephrons arise from mesenchymal renal progenitors that undergo an epithelial transition during the first day of development [ 100 , 101 ], during which time they make lineage decisions based on the genetic cascades that are increasingly being delineated [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. In addition to their favorable anatomical position within the embryo, the nephrons also exhibit genetic and morphological similarities in kidney organogenesis to mammals.…”
Section: Zebrafish As a Model For Podocyte Developmentmentioning
confidence: 99%